POTENSI OBJEK DAN DAYA DUKUNG KAWASAN OBJEK WISATA GOA H'WANG DI KABUPATEN MALUKU TENGGARA - Ongky Safari; C.K. Pattinasaranny; Yosevita. Th. Latupapua (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
The purpose of this study was to determine the potential conditions and carrying capacity of the H'wang Goa object area in Southeast Maluku district. This research uses descriptive research design. The research population is the community that has a relationship with the management of the Goa H'wang object. Samples were taken by purposive sampling as many as 10 people, consisting of Goa managers, ticket sellers, food and beverage seller communities, cave interpreters. Data collection is done through observation, structured interviews, literature studies, and documentation. Data analysis was performed through qualitative and quantitative analysis using weighting / scoring of the attractiveness of objects by using the Object Attraction Analysis Assessment criteria of Goa. The results of the study explain the potential attraction that can be enjoyed by visitors is the panorama around the cave that still seems natural, and has a diversity of species of trees and animals, also supported by the interior of the cave in the form of stalatite and stalamite. The physical carrying capacity of the Goa tourist area to accommodate visitors ranges from 110 people / day. The carrying capacity limit has not exceeded the carrying capacity of the region if it is connected with the number of visits per day which is only around 20-30 visitors.